DEVELOPMENT OF INTEGRATED DIGITAL HR SYSTEM USING WATERFALL FOR LEAVE AND REPORT MANAGEMENT (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2025)
Digitalization in human resource management (HRM) is crucial for modern companies. Several previous studies have discussed HRM, but only a few have focused explicitly on developing leave applications and daily reports, especially regarding comprehensive data recapitulation. Until now, no research has explicitly designed an integrated HRM model incorporating these essential features. In response to this gap, this study presents the design and development of a digital HR management system named “CUTI DULU” to manage leave requests and daily reports. The system was developed Using the Waterfall SDLC model on the Laravel framework to streamline development. It incorporates role-based access control (RBAC) for user permissions and employs JSON Web Tokens (JWT) for secure authentication; data transmission and storage are protected by industry-standard encryption protocols. User Acceptance Testing (UAT) by IT experts and employees verified that the system met functional requirements. Results showed that average leave request processing time fell from four days to about five hours, and administrative errors (e.g. duplicate entries or miscalculations) decreased by 80.95%. Survey responses indicated high satisfaction: 94% of IT experts and 92% of end users reported that the system met their needs. By automating leave and reporting workflows, the proposed system significantly improves administrative efficiency, data transparency, and HR process accuracy.  While these results are promising, the current study is limited to a single organizational context, and its broader applicability remains to be validated. Future work should investigate its adaptability across diverse institutional settings to confirm its scalability and generalizability.
Keywords: entity relationship diagram; human resource management; SDLC; UAT; waterfall